Pengembangan kompetensi pustakawan di Open Library Telkom University - Herlita Meidina (Universitas Pendidikan Indonesia, 2026)
As an information center, the library certainly requires good management so that the information it holds can be stored and used throughout its life. The general objective of this activity is to develop educational professionalism in the field of library and information science that is programmed, guided, collaboratively developed, and integrated. This activity includes three stages: introduction, implementation of activities, and post-implementation, with the service located at the Telkom University Open Library. The program at the Telkom University Open Library includes circulation, reference, and library collection processing services. Circulation services have been performed automatically and documented in the system. The next role is the reference librarian, who masters the reference area and the Bank Indonesia Corner, from the refreshment corner to the reference room, and provides technology services, such as specialized computers for accessing academic final assignments and refinitive. Furthermore, library materials need to go through several stages before they can be served to users. The overall program can run smoothly, although there are some shortcomings and obstacles.